Nonlinear transport of graphene in the quantum Hall regime. (24th October 2016) - Tian, Shibing; Wang, Pengjie; Liu, Xin; Zhu, Junbo; Fu, Hailong; Taniguchi, Takashi; Watanabe, Kenji; Chen, Jian-Hao; Lin, Xi
Abstract: We have studied the breakdown of the integer quantum Hall (QH) effect with fully broken symmetry, in an ultra-high mobility graphene device sandwiched between two single crystal hexagonal boron nitride substrates. The evolution and stabilities of the QH states are studied quantitatively through the nonlinear transport with dc Hall voltage bias. The mechanism of the QH breakdown in graphene and the movement of the Fermi energy with the electrical Hall field are discussed. This is the first study in which the stabilities of fully symmetry broken QH states are probed all together. Our results raise the possibility that the ν  = ±6 states might be a better target for the quantum resistance standard.